Literacies of the Information Society and LIS Education (Training and Practice : Journal of Educational Sciences, 2010)
The requirements of the information society can be met by information literacy and digital literacy. This paper outlines the nature of them, giving insight into their pedagogical models, which should encompass not only skills of finding information but communicative competencies, as well. Library and information science education has to include the main concepts of information literacy and enable that students themselves acquire information literacy skills. This can be supplemented by learning about digital literacy. There is also a need to include academic literacy skills, which is a requirement for general higher education.